If technology is the answer, what does it take?. Issue 3 (2nd April 2016) - Haug, Ruth; Hella, Joseph P.; Nchimbi-Msolla, Susan; Mwaseba, Dismas L.; Synnevag, Gry
ABSTRACT: This article aims to assess why technology such as improved crop varieties has not taken off in Tanzania in spite of substantial efforts, and to consider what role policy plays in that regard. Few farmers use improved varieties due to reasons such as affordability in relation to the low profitability of farming; high risk, including fake seed in the market; and unpredictable policies and marketing opportunities. Effective governance is needed for agriculture to be transformed in the direction stated in national policy documents, but weak institutions and the collective interests of farmers not being sufficiently recognised hinder the likelihood of necessary technological changes happening.